Simulation study on effect of drill pipe eccentricity on cuttings transportation in wellbores based on kinetic theory of granular flow. (18th August 2022) - Wang, Shuyan; Li, Lin; Shao, Baoli; Yuan, Zihan; Xie, Lei; Fan, Jiawei
Abstract: Effective drilling cuttings migration is an important issue in wellbore cleaning. The existing research mainly focuses on the influence of single factors, but lacks targeted research into comprehensive factors affecting on cuttings transport. In present work, the cuttings migration carried by drilling fluid in the wellbore is simulated using Eulerian-Eulerian two-fluid model with the kinetic theory of granular flow. The granular temperature of cuttings, solids pressure and solids viscosity in the annulus are obtained to determine interaction between cuttings particles, involving the fluctuation and stress of cutting particles in wellbore. Effects of drill pipe rotating speed and inlet velocity of drilling fluid in different wellbore inclinations under different eccentric conditions on the efficiency of cuttings migration are analyzed. Simulation results reveal that comprehensive consideration of drill pipe eccentricity and well inclination, increasing rotational speed of drill pipe and inlet velocity of drilling fluid can result in reduction in the cuttings bed height and rise in the efficiency of cuttings migration within limits. Increasing the inlet velocity of drilling fluid is more positive effect to cuttings migration in the inclined wellbore with eccentricity, while increasing rotational speed is more beneficial to improve efficiency of cuttings migration at the horizontal wellbore.